2022
DOI: 10.3389/fonc.2022.899404
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Sequence MR-Based Radiomics Signature for Predicting Early Recurrence in Solitary Hepatocellular Carcinoma ≤5 cm

Abstract: PurposeTo investigate the value of radiomics features derived from preoperative multi-sequence MR images for predicting early recurrence (ER) in patients with solitary hepatocellular carcinoma (HCC) ≤5 cm.MethodsOne hundred and ninety HCC patients were enrolled and allocated to training and validation sets (n = 133:57). The clinical–radiological model was established by significant clinical risk characteristics and qualitative imaging features. The radiomics model was constructed using the least absolute shrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…These findings may be beneficial for choosing optimal and individualized treatment strategies for HCC patient. The radiomics model different, and their contributions to the combined model are also different [26]. Multisequence combined models have been shown to have better prediction efficiency [10,11,[27][28][29], consistent with our present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings may be beneficial for choosing optimal and individualized treatment strategies for HCC patient. The radiomics model different, and their contributions to the combined model are also different [26]. Multisequence combined models have been shown to have better prediction efficiency [10,11,[27][28][29], consistent with our present study.…”
Section: Discussionsupporting
confidence: 89%
“…the most preserved, consistent with previous studies [10,30]. Among the 7 optimal features of the combined model, there were six features from FS-T2WI and one feature from DCE-MRI; thus, there were more features from FS-T2WI than from contrast-enhanced sequences, which is inconsistent with the literature [26,31]. The main reason for this may be that other contrast-enhanced sequences, such as those from the delayed phase and the hepatobiliary phase, were not included in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have reported that radiomics may be helpful to the preoperative prediction of early recurrence of HCC, we selected 15 representative papers and compared them with our study in terms of imaging modality, number of included patients, modeling methods, etc. From the perspective of image modality, CT(n=6) (6,20,21,(32)(33)(34) has higher specificity than MRI (n=9) (7,(35)(36)(37)(38)(39)(40)(41)(42). In our study, we used CECT which hold fixed and uniform parameters than MRI to predict early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies -including ten studies on HCC (88)(89)(90)(91)(92)(93)(94)(95)(96)(97), four studies on Mass-forming CC (98-101), and three studies on colorectal liver metastases (102-104)-utilized various radiomics approaches to predict outcomes and guide treatment decisions. The studies involved diverse cohorts, including patients undergoing liver transplantation, surgical resection, or chemotherapy.…”
Section: Prognosticationmentioning
confidence: 99%
“…The endpoint outcomes ranged from overall survival (OS), recurrence free survival (RFS), progression-free survival (PFS), event-free survival (EFS), early recurrence (ER), 1-year survival and 5-year survival, post-hepatectomy liver failure (PHLF), and lymph node metastasis. The AUCs for predictive models varied, ranging between 0.70 to 0.98 (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Moreover, the integration of radiomics with clinical factors consistently improved predictive performance, demonstrating the potential for personalized risk assessment.…”
Section: Prognosticationmentioning
confidence: 99%